The Black girl survives in this one : horror stories - Evans, Desiree S.; Fennell, Saraciea J.; McKinney, L. L. (Leatrice L.); Nash, Kortney; Adams, Erin E.; Evans, Desiree S.; Harris, Zakiya Dalila; Ireland, Justina; Hermon, Daka; Morris, Brittney; Aaron, Camara; Moulite, Maika; et al. (Flatiron Books, 2024)
A collection of fifteen horror stories centering on Black girls who battle monsters, both human and supernatural, face down death, and survive.